P092 Humoral and T cell responses to COVID-19 vaccination in IBD. (21st January 2022) - Zhang, E; Bond, K; Nguyen, O; Allen, L; Kedzierski, L; Kedzierka, K; Christensen, B
Abstract: Background: The characteristics of SARS-CoV-2 vaccine-induced immunity in inflammatory bowel disease (IBD) patients on immune modifying agents has not been clearly defined due to their exclusion in vaccine trials. Emerging results suggest infliximab impairs antibody response compared to vedolizumab. However there has not been direct comparison to controls. We evaluated this with both humoral and T cell response in IBD patients. Methods: Antibody and T cell response were analysed in IBD patients who received BNT162b2 (Pfizer–BioNTech) or ChAdOx1 nCoV-19 (Oxford–AstraZeneca) vaccination from a single Australian centre. The control group were healthcare workers (HCW) without IBD. Blood samples were taken at 4 time points: at baseline V0 (before vaccination); V1 (7–14 days after vaccine 1); V2 (7–14 days after vaccine 2); V3 (21–42 days after vaccine 2). Antibodies to the S1/2 IgG subunit and receptor-binding protein (RBD) were measured and reported here. Results: 88 (28 ulcerative colitis, 50 Crohn's disease) IBD patients were included and compared to 53 healthy controls (Table 1). IBD patients medications included 6 5ASA (6.8%), 6 immunomodulator monotherapy (6.8%), 14 anti-TNF monotherapy (15.9%), 32 anti-TNF combination therapy with immunomodulator (36%), 16 IL12/23 (18%) and 13 vedolizumab (14%). Pre-vaccine baseline sera showed absence of anti-RBD antibodies in all participants. 84 patients (87%) received BNT162b2 and 4 (4.5%) received ChAdOx1 nCoV-19 vaccines. Geometric mean [SD] anti-S1/2 antibody concentrations at 4 weeks after second vaccination (V3) were significantly lower in IBD TNF treated patients (162.6[1.7]) compared to IBD non TNF treated patients (325.2[1.3]), and healthy controls (325.2[1.3]), p<0.0001 (Figure 1). There was no difference between non-TNF treated patients including those on vedolizumab or IL12/23 compared to controls. Similarly there was a significant difference between anti-RBD IgG titres between TNF and non-TNF IBD patients at V3 but not when compared to controls (Figure 2). There was no difference in RBD IgG and anti-S1/2 antibodies between anti-TNF monotherapy and combination anti-TNF with immunomodulator. All IBD and healthy controls seroconverted at V3 (Figure 3). Conclusion: TNF agents influence SARS-CoV-2 vaccine-induced antibody response in IBD patients, with lower anti-S1/2 IgG concentrations compared to non-TNF IBD patients and healthy controls. However, there was no difference in RBD IgG titres between controls and IBD patients overall. It is unclear whether these subtle differences in antibody response in IBD patients on TNF agents is biologically meaningful, as all groups seroconverted after second dose vaccination. Neutralising antibody and T cell data (CD4+/CD8+) from this study to come.